THE INFLUENCE OF FOOD RELATED BEHAVIOR AND PHYSICAL ACTIVITY ON THE DEVELOPMENT OF METABOLIC SYNDROME IN YOUNG ECONOMICALLY ACTIVE POPULATION LIVING IN THE FAR NORTH AREAS - E. V. Korneeva; N. E. Trekina; А. А. Mamina (Кардиоваскулярная терапия и профилактика)
Aim. To assess the changes in food related behavior, physical activity (PA) in patients with metabolic syndrome (MS) related to the gender, duration of living on territories equal to the Far North. Material and methods. Totally 183 patients with MS and 65 healthy volunteers studied at the age 18-40 y.o., for 3 living in Khanty-Mansiysky Autonomic District — Yugra. Questionnaire DEBQ used to assess changes in food consumption behavior. PA assessed with questionnaires on general health, that is recommended RAMS SI National Scientific- Research Institute of Population Health and European Regional WHO bureau (2005).Results. Almost all patients studied had been living in the north for more than >10 years. Food related disorders of behaviour were found in 86,7%. Among women there were emotiogenic (41,3%) or restrictive (30,8%) types of disorder. In 50,5% men the main was external type of disorder. While following recommendations quantity of women with restrictive type increased by 47,9%. Among men with MS not following recommendations the quantity of those with external type also increased (by 22,7%). Most of the participants had average weekly PA. Men without MS treatment and with hypodynamia got 14,9% more, than women without MS treatment. During follow up their PA increased 21,1% of men with MS.Conclusion. Individual opportunities and behavior predetermines the main principals of life supporting system and attitude to the self-health of novel inhabitants of the Far North. Therefore it is necessary to improve prevention among inhabitants by their healthy life style compliance.